An Experimental Study on the Performance of Calcium Carbonate Extracted from Eggshells as Weighting Agent in Drilling Fluid - Iqbal, R.; Zubair, M.; Pirzada, F.; Abro, F. N.; Ali, M.; Valasai, A. (Engineering, Technology & Applied Science Research, 2019)
Drilling mud density is an important factor in drilling operations. The cost of the drilling mud used for oil and gas well drilling can be 10%-15% of the total drilling cost, and the deeper the well, the more the needed drilling mud. This research aims to prepare a mud that provides performance similar to the conventional mud and to lower down the dependency of primitive CaCO3 technology by exploring it from trash/polluted and naturally occurring materials. For that purpose, a mud was prepared by replacing primeval CaCO3 with the CaCO3 derived from eggshells, as eggshells contain CaCO3 in high amounts which range from 70% to 95%. The success of this project will provide an affordable solution and an alternative way to explore new methodologies for obtaining CaCO3. According to the 2017 Report of Pakistan Poultry Association (PPA) 18,000 Million table eggs are consumed per year in Pakistan. The obtained results of this research are quite satisfactory. CaCO3 obtained from eggshells is used in high amounts, 275–410g to achieve density ranges from 9.5 to 11.0 pounds per gallon whereas, pure the needed quantity of pure CaCO3 is 150g to obtain the density of 10.5 pounds per gallon. Apart from this, it is also observed that eggshell based CaCO3 samples are more efficient in rheological properties compared to the market samples of CaCO3 t. The pH of pure CaCO3 sample of 10.5 pounds per gallon density is almost the same with the sample of eggshell CaCO3 of 10.5 pounds per gallon density.